2013
DOI: 10.1113/expphysiol.2012.070888
|View full text |Cite
|
Sign up to set email alerts
|

Viscerosympathetic reflexes in human spinal cord injury: relationships between detrusor pressure, blood pressure and skin blood flow during bladder distension

Abstract: New Findings r What is the central question of this study?Dangerous increases in blood pressure (autonomic dysreflexia) can be caused by visceral stimuli in spinal cord injury, but it is not known how cutaneous vasoconstriction is related to increases in bladder and blood pressures during bladder distension. r What is the main finding and its importance?We show that an increase in bladder pressure causes cutaneous vasoconstriction in the fingers that is inversely related to the bladder pressure. Skin blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…However, we can infer from the cystoscopy that gravity filling of the bladder resulted in only 150 ml of bladder volume filling, much lower than the volume (up to 500 ml) instilled by continuous pump during urodynamics. In our 21 subjects, the bladder filling during urodynamics induced detrusor pressure (average 44.1±29.8 cm H 2 O), which was consistent with the study by Wallin et al 17 However, in this study investigators reported a positive correlation (r ¼ 0.52, Po0.05) between the maximal detrusor pressure and the maximal increase in BP. This correlation was not present in our study.…”
Section: Discussionsupporting
confidence: 42%
“…However, we can infer from the cystoscopy that gravity filling of the bladder resulted in only 150 ml of bladder volume filling, much lower than the volume (up to 500 ml) instilled by continuous pump during urodynamics. In our 21 subjects, the bladder filling during urodynamics induced detrusor pressure (average 44.1±29.8 cm H 2 O), which was consistent with the study by Wallin et al 17 However, in this study investigators reported a positive correlation (r ¼ 0.52, Po0.05) between the maximal detrusor pressure and the maximal increase in BP. This correlation was not present in our study.…”
Section: Discussionsupporting
confidence: 42%
“…Detrusor pressure seems to be a trigger for AD in patients with bladder distension (not the bladder volume). Wallin et al have shown that in patients with SCI above T4, changes in bladder pressure correlate positively with changes in blood pressure and inversely with changes in pulse rate, whereas in control subjects without SCI, these changes are not shown. Furthermore, Yoshizawa et al used an experimental model in rats with SCI above Th5.…”
Section: Discussionmentioning
confidence: 99%
“…So, if the patient has not an indwelling catheter, the catheterization of the urinary bladder is indicated. 34 40 Because any manipulation with a urinary catheter can start an AD reaction, it should be performed in local anesthesia utilizing 2 to 3 minutes instillation of trimecaine hydrochloride or lidocaine hydrochloride lubricating jelly into the urethra 40 71 72 If the urinary bladder is empty, but symptoms of AD persist, the fecal impaction of the distal colon must be suspected. The complete bowel evacuation after mucosal anesthesia should, therefore, follow.…”
Section: Management Of Autonomic Dysreflexiamentioning
confidence: 99%
“…The complete bowel evacuation after mucosal anesthesia should, therefore, follow. 67 69 71 If the aforementioned measures do not alleviate symptoms and reduce blood pressure sufficiently, pharmacological management must be initiated. 39 40 Because the administration of antihypertensive drugs in patients with unstable cardiovascular functions may lead to sudden hypotension, the selection of medicaments, as well as their initial dosage should be cautious and attended by monitoring blood pressure every 2 to 5 minutes for at least 2 hours after resolution of AD episode.…”
Section: Management Of Autonomic Dysreflexiamentioning
confidence: 99%